2021
DOI: 10.1021/acsestwater.1c00153
|View full text |Cite
|
Sign up to set email alerts
|

Reconciliation of Spatiotemporal Influences on Two-Dimensional Distribution and Fate of Emerging Contaminants in a Subtropical River

Abstract: This study involves elucidation of spatial and temporal influences on horizontal and vertical distribution and fate of contaminants of emerging concerns (CECs) in riverain systems. In total, 23 CECs encompassing antibiotics, nonantibiotic drugs, and bisphenol analogues were detected. The antibiotic concentrations were relatively higher in deep water than in surface water. Spatial connectivity and spatial autocorrelation suggested the occurrence and concentration of the majority of the CECs devoid of neighborin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Similarly, Rashid et al. (2021) reported a negative correlation of BPA with electrical conductivity.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Similarly, Rashid et al. (2021) reported a negative correlation of BPA with electrical conductivity.…”
Section: Resultsmentioning
confidence: 78%
“…Gong et al (2019) have observed a negative correlation between the salinity of the water and BPA. Similarly, Rashid et al (2021) reported a negative correlation of BPA with electrical conductivity.…”
Section: Persistance Of Bpa and Its Relationship With Water Quality P...mentioning
confidence: 87%
“…Based on decreasing pattern of dissolved oxygen (DO) during stratified seasons, water columns were split into two zones: the shallow zone (0-10 m) with the average DOs higher than 3 mg/L, and the deep zone (20-53 m) with the average DOs lower than 3 mg/L. A total of 16 physico-chemical parameters and 22 micropollutant compounds were measured previously 24 , from which the most frequently detected micropollutants (> 30%; 17 micropollutants) were included in further analysis ( Table S1 ). Water samples (500 – 1,000 mL) were filtered through 3 μm filters and 0.22 μm filters to get size-fractionated sub-samples for DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…This is specifically done through the use of the Laplacian matrix, which captures the network topology and the interaction between adjacent sites through the advection process. The use of spatial (topological) relationships is not new, notably, the well-known Moran [4] and Geary [5] spatial correlation coefficients, as well as, their recent updated developments [ 6 , 7 ] have been widely used in many domains, including the aquatic environment [8] , [9] , [10] , [11] , [12] , [13] , [14] . Our approach allows obtaining relevant quantitative information relative to the dynamics of the measured contaminants such as the relative importance of the two main processes involved, i.e., the conservative transport across the aquifer vs. the local depletion, which gives a glimpse into their persistence.…”
Section: Introductionmentioning
confidence: 99%